RISK FACTORS IN THE OCCURRENCE OF CHOLELITHIASIS IN CHILDREN AND ADOLESCENTS: A SINGLE-CENTER EXPERIENCE - Radlović, Vladimir (Medical Research, 2024)
Introduction: Cholelithiasis is etiopathogenetically very heterogeneous and, in terms of frequency, a rare disease in the period of growth and development. The aim of the study was to analyze risk factors for the occurrence of cholelithiasis in that age of life.Material and Methods: This retrospective study included 80 children and adolescents, 50 female and 30 male, aged 4-18 (14±5.55) years, with symptomatic cholelithiasis who were operated on at the University Children's Hospital in Belgrade in the period from 2000 to 2016. The diagnosis of the disease was based on the ultrasound findings. Data on risk factors for the development of biliary calculosis were obtained from medical history.Results: In 46 (57.5 %) patients predisposing risk factors for cholelithiasis were verified. One risk factor was identified in 34 patients, two risk factors were identified in 10 patients, three risk factors were identified in two patients, while in others risk factors were not identified. Family predisposition to cholelithiasis was registered in 28 (35%) patients, obesity in 10 (12.5%), preobesity in nine, rapid weight sloss in four, hereditary hemolytic disease in two, and premature birth combined with parenteral nutrition and sepsis as a complication in two patients. Apart from those born prematurely, another 10 patients had combined risk factors for cholelithiasis, six patients had family predisposition and obesity, and four patients had obesity and self-initiated rapid weight loss programme.Conclusion: According to our research, the most common risk factors for cholelithiasis in children and adolescents are family predisposition and excess body weight. Most of the patients belonged to the adolescent age and female gender.
Keywords: cholelithiasis; risk factors; children; adolescents